Polish mathematicians and mathematics in World War I. Part I: Galicia (Austro-Hungarian Empire) - Stanisław Domoradzki; Małgorzata Stawiska (Studia Historiae Scientiarum)
In this article we present diverse experiences of Polish mathematicians (in a broad sense) who during World War I fought for freedom of their homeland or conducted their research and teaching in difficult wartime circumstances. We discuss not only individual fates, but also organizational efforts of many kinds (teaching at the academic level outside traditional institutions, Polish scientific societies, publishing activities) in order to illustrate the formation of modern Polish mathematical community.